Design and simulation of microfluidic smart bandage using Comsol Multiphysics - et. al., Priti Rajput, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Microfluidics is an emerging field finding its applications in biomedical engineering for investigations of cellular micro structures. Human body is composed of 70% of water having thin and fine structure of microfluidic blood channels spread throughout the body. These microchannels supply essential nutrients to each part of the body at right time and in right amount. Microfluidics is the science of controlling and manipulating the fluid in micro channels. Manipulating the flow through the microchannels is useful for developing electronic devices, artificial human body parts, and economical diagnostics tools. Microfluidics also helps in manufacturing of pharmaceuticals and carrying out precise chemical analysis of complex systems. A number of diagnostic devices and artificial human organs like lungs, heart, kidneys, etc. have been simulated using microfluidics for developing easy, economical, non-invasive, and rapid method of drug testing. Recently, its applications have also been investigated in smart bandage design. Further, blend of microfluidics with herbal medicines is expected to enhance the healing along with negligible side effects unlike allopathic treatments. The scope of the present research is to develop a smart bandage capable of sensing the status of the wound and supplying required amount of drugs using microfluidic channels. The flow rate of drugs through microchannels is simulated using the physics of laminar flow, capillary action, and diffusion phenomena for optimizing the size and shape of the constituent components of the bandage like microfluidic channels, mixers, and porous material used for drug distribution with in the active area of the bandage. The analysis of the results shows that the mixer having inner radius as 150 microns and outer radius as 250 microns is sufficient to mix the incoming drugs via inlets of 50 microns’ diameter. Results also show that capillary action dominates the diffusion phenomenon for supplying the drugs to the wound. The investigations of the prototype show that a smart bandage having the provisions of uniform drug distribution, automatic control, on board pH, moisture, O2 measurement, and dc current based healing mechanism is possible to be incorporated with in a comfortable size for fast wound healing.